Analysis of the Needs of Developing Teaching Materials in the Form of STEM-Based Web Modules Using Scaffolding - Menza Hendri; Dian Pertiwi Rasmi; Winda Ananda (Postgraduate, University of Mataram, 2021)
Since the Coronavirus disease (COVID-19) pandemic, the world of education has been affected by the application of a learning system that is carried out in a blended learning manner. Therefore, this study aims to develop teaching materials in the form of a STEM-based web module using scaffolding to assist the learning process during the covid 19 pandemic. The development of a STEM-based web module using scaffolding is carried out using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Data were obtained through interviews with physics teachers. Based on the results of interviews with teachers at one of the senior high schools in Batanghari district, it is known that in offline learning, printed books from the school library are still used. Therefore, we need an electronic module that can be accessed anytime and anywhere to facilitate the learning process. So that researchers will develop a STEM-based web module using scaffolding on straight motion physics material for class X high school. The product produced is in the form of a web containing material for straight motion physics class X SMA/MA based on STEM using scaffolding